Autophagy of naïve CD4+T cells in aging - The role of body adiposity and physical fitness - Padilha, Camila S. [UNESP]; Kushkestani, Mehdi; Baptista, Liliana P.; Krüger, Karsten; Lira, Fábio Santos [UNESP] (Cambridge University Press (CUP), 2023)
Life expectancy has increased exponentially in the last century accompanied by disability, poor quality of life, and all-cause mortality in older age due to the high prevalence of obesity and physical inactivity in older people. Biologically, the aging process reduces the cell's metabolic and functional efficiency, and disrupts the cell's anabolic and catabolic homeostasis, predisposing older people to many dysfunctional conditions such as cardiovascular disease, neurodegenerative disorders, cancer, and diabetes. In the immune system, aging also alters cells' metabolic and functional efficiency, a process known as 'immunosenescence', where cells become more broadly inflammatory and their functionality is altered. Notably, autophagy, the conserved and important cellular process that maintains the cell's efficiency and functional homeostasis may protect the immune system from age-associated dysfunctional changes by regulating cell death in activated CD4+ T cells. This regulatory process increases the delivery of the dysfunctional cytoplasmic material to lysosomal degradation while increasing cytokine production, proliferation, and differentiation of CD4+ T cell-mediated immune responses. Poor proliferation and diminished responsiveness to cytokines appear to be ubiquitous features of aged T cells and may explain the delayed peak in T cell expansion and cytotoxic activity commonly observed in the 'immunosenescence' phenotype in the elderly. On the other hand, physical exercise stimulates the expression of crucial nutrient sensors and inhibits the mechanistic target of the rapamycin (mTOR) signaling cascade which increases autophagic activity in cells. Therefore, in this perspective review, we will first contextualize the overall view of the autophagy process and then, we will discuss how body adiposity and physical fitness may counteract autophagy in naïve CD4+ T cells in aging.
Keywords: Age; autophagy; naïve cells; obesity; physical exercise